The GERD: National Interests – Diplomatic Negotiations – Current and Future Challenges: سد النهصة: مصالح قومية – مفاوضات دبلوماسية – تحديات آنية ومستقبلية - Al-Naggar, Abdallah Abdel-Ati; Prantner, Zoltán (Études sur la Région Méditerranéenne, 2022)
The Nile and Egypt form an inseparable entity. The river played an unneglectable role in the formation and survival of the Egyptian civilizations, providing more than 90% of the state’s freshwater needs. Simply, there is no country in all over the world whose existence depends on the water of a river such as Egypt: it is arguably more heavily dependent on the Nile than any other country. The dam built by Ethiopia along the Nile could therefore lead to a serious water crisis in Egypt. Accordingly, Cairo considered the situation so critical. At the same time, Ethiopia’s priority is to ensure its own economic development, rather than the stability of the region. It hopes to implement the latter from Africa’s largest hydropower plant to date, the Grand Ethiopian Renaissance Dam (GERD).